2011
DOI: 10.1017/s0022215111002507
|View full text |Cite
|
Sign up to set email alerts
|

Are laryngeal squamous cell carcinoma incidence and patient mortality a function of ABO blood grouping? A retrospective study

Abstract: Although our findings show no association between blood group and five-year survival, these results are inconclusive, and warrant further study of the association between blood type and laryngeal (and other) head and neck cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 7 publications
(17 reference statements)
2
8
1
5
Order By: Relevance
“…For salivary gland cancer patients also, blood group A was found in majority of the patients which is contrary to the results of Garrett JV et al, in which no significant relation was found between blood group and salivary cancer [25]. However, Laryngeal cancer was found to be more in blood Group B which is contradictory to the results by Adam SI et al, who showed a higher prevalence among patients with blood Group A [26]. No specific reason has been documented so far for the prevalence of specific blood groups among various head and neck cancers.…”
Section: Resultscontrasting
confidence: 72%
“…For salivary gland cancer patients also, blood group A was found in majority of the patients which is contrary to the results of Garrett JV et al, in which no significant relation was found between blood group and salivary cancer [25]. However, Laryngeal cancer was found to be more in blood Group B which is contradictory to the results by Adam SI et al, who showed a higher prevalence among patients with blood Group A [26]. No specific reason has been documented so far for the prevalence of specific blood groups among various head and neck cancers.…”
Section: Resultscontrasting
confidence: 72%
“…Our current large cohort study made up for the deficiencies in previous studies, and the results showed that blood group had no prognostic value. A similar non-significant association has also been reported in laryngeal cancer [9]. Two reasonable explanations may account for these non-significant results.…”
Section: Discussionsupporting
confidence: 75%
“…Relationship between the ABO blood group and prognosis have been reported in many tumor types, including breast cancer [4], pancreatic cancer [5, 6], esophageal squamous cell carcinoma [7, 8], laryngeal squamous cell carcinoma [9] and non-small cell lung cancer [10]. Seemingly, the ABO blood group may be a useful prognostic factor and it also plays an important role in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of novel prognostic factors to recognise patients at high risk is warranted. Recently, the associations between ABO blood group and survival have been evaluated in pancreatic cancer (Engin et al , 2012; Rahbari et al , 2012), locoregional renal cell carcinoma (Kaffenberger et al , 2012), triple-negative breast cancer (Yu et al , 2012) or breast cancer (Stamatakos et al , 2009; Gates et al , 2012), oesophageal squamous cell carcinoma (Nozoe et al , 2004), and laryngeal squamous cell carcinoma (Adam et al , 2012). …”
mentioning
confidence: 99%